Mosses from an old manse : stories - Hawthorne, Nathaniel, 1804-1864 (Open Road Media, 2016)
"Whatever Nathaniel Hawthorne may hereafter write, Mosses from an Old Manse will ultimately be accounted his masterpiece."--Herman Melville Aylmer is an inventor, the greatest of his age. But his heart is torn between his devotion to science and his love for his beautiful wife, Georgiana, whose appearance would be perfect were it not for the small red birthmark on her cheek. Unnaturally obsessed with the blemish, Aylmer sets out to erase it from his beloved's face-and discovers that his heedless quest to master Nature has disastrous consequences. A Gothic romance both chilling and tragic, "The Birthmark" is just one of the masterworks of short fiction in this classic collection, which also includes "Young Goodman Brown," "Rappaccini's Daughter," and the pioneering work of alternative history, "P.'s Correspondence." First published in 1846, Mosses from an Old Manse reveals Nathaniel Hawthorne to be a visionary far ahead of his time, and one of the most haunting voices in American literature. This ebook has been professionally proofread to ensure accuracy and readability on all devices.